PENGARUH POLIFENOL TEH HIJAU TERHADAP PRODUKSI TNF-A (TUMOUR NECROSIS FACTOR-A) PADA KULTUR SEL TROFOBLAS MANUSIA YANG DIPAPAR GLUKOSA TINGGI 33 Mm - Aisah, Siti; Djati, Sasmito; Khotimah, Husnul (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2010)
The purpose of this research was to study the effect of green tea polyphenol to TNF-á production on human trophoblast cell culture exposed by 33 mM glucose. Trophoblast culture isolated from human fetal placental tissue by sectio caessaria. Monolayer trophoblast cells that had been incubated for 3 days at 5% CO2; 37°C were divided into 2 groups: (1) normal glucose (5 mM) and (2) glucose 33 mM exposure, both divided into 2 sub groups: (a) without green tea polyphenol treatment, and (b) green tea polyphenol treatment 0,1; 0,2; and 0;4 mg/ml. Cells incubated for 3 days at 5% CO2; 37°C then analyzed cytotrophoblast cells characteristic. TNF-á level was measured by ELISA and analyzed with oneway ANOVA. Immunocytochemistry showed the number of cells that expressed TNF-á then analyzed descriptively. The results of this study showed that TNF-á level at 0,1; 0,2; and 0,4 mg/ml polyphenol were 2804,333 ñg/mL; 2513,222 ñg/ml; and 2739,889 ñg/ml respectively compared with 2739,889 ñg/mL normal glucose without polyphenol, and 2721,000 ñg/mL; 2612,111 ñg/mL; and 2566,555 ñg/mL compared with 2621,000 ñg/mL glucose 33 mM exposure without polyphenol. Number of cells that expressed TNF-á with 0,1; 0,2; and 0,4 mg/ml polyphenol treatment were 0%; 2%; and 5,5% compared with 0% normal glucose without polyphenol, and 82%; 0%; and 0% compared with 3% glucose 33 mM exposure without polyphenol. Green tea polyphenol exposure for 3 days at 0,1; 0,2; and 0,4 mg/ml didn’t significantly affect the decreasing of TNF-á production. Keywords: GDM, green tea, polyphenol, TNF-á, trophoblast